Optimising power transmission options for marine energy converter farms. (September 2016) - Nambiar, Anup J.; Collin, Adam J.; Karatzounis, Sotirios; Rea, Judy; Whitby, Ben; Jeffrey, Henry; Kiprakis, Aristides E.
Highlights: A techno-economic analysis framework to assess transmission options for MEC farms. Supply quality constraints and sizing of reactive power compensation included in assessment. The economic viability of transmission options measured based on component and operational costs. The developed framework tested with a range of MEC farm sizes and distances from the shore. The results provide guidance for transmission system design. Abstract: This paper introduces a techno-economic analysis framework to assess different transmission options for marine energy converter (MEC) farms. On the technical front, the feasibility of the transmission options considering supply quality constraints and the optimal sizing of reactive power compensation to allow maximum real power transfer capability in the subsea transmission cable have been considered. The economic viability of different transmission options are measured based on component costs and the costs associated with the transmission losses. A case study has been presented in the paper, which demonstrates the application of this techno-economic analysis framework on a range of MEC farm sizes and distances from the shore. The results characterise the performance of different transmission system options with respect to three key design parameters – distance to shore, array power and transmission voltage – and provide guidance for system design.